Cluster Preface: Japan/Netherlands Gratama Workshop - Fukase, Koichi (Synlett, 2024)
is an Executive Vice President at Osaka University and a full Professor at the Graduate School of Science. He received his B.Sc. in Chemistry from the Faculty of Science, Osaka University in 1982, and his Ph.D. in Chemistry from the same university in 1987. After working as a Research Fellow of the Japan Society for the Promotion of Science for about one year, he became an Assistant Professor at Faculty of Science, Osaka University in 1988. In 1994, he joined the Department of Chemistry at Columbia University as a Research Fellow. He was promoted to Lecturer in 1996, Associate Professor in 1998, and Full Professor in 2004 at Graduate School of Science, Osaka University. From 2020 to 2024, he was the Dean of the Graduate School of Science, Osaka University. In 2024, he was appointed as an Executive Vice President. His research interests include carbohydrate chemistry, organic synthesis, chemical biology, glycobiology, innate immunity, and targeted radionuclide therapy. He received the Chemical Society of Japan Award For Young Chemists in 1994, the Chemical Society of Japan Award for Creative Work in 2011, Honorary Life Membership in the International Endotoxin and Innate Immune Society in 2021, and the Chemical Society of Japan Award in 2024.